A New Standard for Care during Postpartum. Issue 4 (July 2021) - Killion, Molly M.
Abstract : Several important studies have recently been published about care during postpartum. Our maternity nursing expert, Molly Killion, covers the new evidence and explains the implications for clinical practice.